Tachlīlu Manhaji Kitābati al-‘Arabiyyah fī Kurrāsati ath-Tharīqti al-Chamīdiyyati fī Tachsīni al-Kitābati al-I’tiyādiyyati - Ahmad Yasir Amrulloh; Ato'illah Ato'illah (Universitas Negeri Malang, 2023)
The lack of learners in understanding Arabic writing rules properly makes it difficult for them to write Arabic-based texts, especially those with beginner backgrounds from the lay community, so special methods are needed to deal with these problems. The purpose of this research is to find out the methods contained in Kurrasah al-Thariqah al-Hamidiyah fi tahsin al-Kitabah al-I'tiyadiyah. This type of research is a literature study using qualitative procedures. As primary data, the author refers to the kurrasah to get the methodology that the author's idea. While secondary data are taken from documents, journals, reports, and books related to the study. Then the data is described narratively. As for the analysis, the author uses the Miles and Huberman model technique, namely reducing data, presenting data, and drawing conclusions. Data reduction is used to summarise and select the author's main idea in compiling the kurrasah. While in the presentation, the author will present the findings and discuss them with research that supports the findings that have been formulated. Meanwhile, the conclusion is used by the author as a step to answer the focus of the study written at the end of the research process. The results of this study show that the methods contained in Kurrasah include several methods used in learning Arabic writing, including grouping methods, repetition and guided practice methods, assignment and drill methods, and inquiry methods. Thus, learning using Kurrasah al-Thariqah al-Hamidiyah fi tahsin al-Kitabah al-I'tiyadiyah becomes the right alternative to teach Arabic writing techniques properly and correctly.